PERAN LEMBAGA MANAJEMEN KOLEKTIF NASIONAL DALAM PERLINDUNGAN HAK CIPTA LAGU PENGEMIS YANG DIGUNAKAN OLEH STASIUN TELEVISI INDOSIAR TANPA SEIZIN PENCIPTANYA - Grace Kezia Caroline; R. Rahaditya (Jurnal Hukum Adigama, 2022)
Intellectual Property Rights will be rights that arise or are brought into the world from human intellectual abilities.The term Intellectual Property Rights comes from the word Intellectual Eigendom Recht in Dutch within theframework of Continental Europe. Intellectual Property Rights have been used for quite a long time, especially byjournalists such as Sudargo Gautama, C.S.T. Kansil, Muhammad Djumhana. Intellectual property rights areselective and direct which implies that they can protect anyone who has these rights. Anyone can be charged withviolating this right. The National Collective Management Institute (LMKN) is an organization that has the authorityto collect figures for the use of songs and music that are protected from business clients on a non-permanent basisand ratified by the Decree of the Minister of Law and Human Rights. Along with the progress of the times, followedby the expansion of human needs because of their lifestyle. One of the signs is the increasing interest and enthusiasmof the public in general in the field of entertainment, especially songs. The lawsuit for the use of a song without acopyright to the song's creator surfaced on April 4, 2021. The lawsuit was recorded by a lyricist who was not abeggar of love, popularized by Jhonny Iskandar, Haji Ukat Sukatna, to indosiar.